A nova gestão pública e a inovação no Brasil: um estudo sobre a Empresa Brasileira de Pesquisa e Inovação Industrial (EMBRAPII) - Azevedo, Ana Carolina Silva de (2023)
This research investigates how Brazil fosters innovation in the productive sector, focusing on the EMBRAPII model. A case study was conducted, based on document analysis and interviews. The research examines EMBRAPII's management contracts and suggests improvement recommendations for its indicators. The study discusses a differentiated funding model for research, development, and innovation - RD&I, highlighting the need for new ways to measure the innovative performance of the funding agency.